AurOrGlass: ORMOSIL Sol‐Gel Glasses Functionalized with Gold Nanoparticles for Advanced Optical Applications. Issue 30 (8th August 2019) - Ciriminna, Rosaria; Fidalgo, Alexandra; Ilharco, Laura M.; Pagliaro, Mario
Abstract: Dubbed AurOrGlass in this study for the first time, organically modified sol‐gel glasses functionalized with Au nanostructures and atomic clusters are endowed with exceptional optical properties. The behaviour of these plasmons is governed by key nanochemistry and physical principles addressed herein prior to their widespread adoption in several technological domains. Abstract : AurOrGlass, namely organically modified sol‐gel glasses functionalized with Au nanostructures and atomic clusters, are endowed with exceptional optical properties. Their behaviour is governed by key nanochemistry and physical principles addressed in this study prior to their widespread adoption in several technological domains.